Accounting, inequality and COVID-19 in Australia. Issue 6 (29th April 2021) - Andrew, Jane; Baker, Max; Guthrie, James
Abstract : Purpose: The authors explore the Australian Government's implementation of budgetary measures to manage the social and economic impacts of COVID-19, paying particular attention to how the country's history of inequality has shaped these actions, and the effect inequality may have on outcomes. Design/methodology/approach: In this qualitative case study of public budgeting, the authors draw on the latest research into inequality to consider the implications of policy responses to COVID-19 in Australia. In particular, we examine the short-term introduction of what we term "people-focused" budgetary measures. These appeared contrary to the dominant neoliberalist approach to Australian welfare policymaking. Findings: This paper foregrounds the relationship between budgeting, public policy and inequality and explores how decades of increasingly regressive tax systems and stagnating living wages have made both people, and the state, vulnerable to crises like COVID. Social implications: There is still much to learn about the role of accounting in the shaping of growing economic inequality. In focusing on public budgeting within the context of COVID, the authors suggest ways accounting researchers can contribute to our understanding of economic inequality, both in terms of drivers and consequences. The authors hope to contribute to a growing body of accounting research that can influence social movements, political debates and policymaking, while also raising awareness of the consequences of wealth and income inequality. Originality/value: The authors explore ways accounting scholars might help articulate a post-COVID future that avoids recreating the inequalities of the past and present.